The Relationship of Strengthening Gift Of Christian’s Education Teacher With Students Learning Motivation for Class VI Students of SD Negeri 173105 Tarutung, North Tapanuli Regency Year 2019 - Andrianus Nababan (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
ABSTRACTThe research is aimed to determine the relationship of strengthening the gift of Christian education teacher with students learning motivation for class vi students of sd negeri 173105 tarutung, north tapanuli regency year 2019.  The research hypothesis was that there was a positive and significant relationship of strengthening gift of Christian education teacher with students learning motivation for class vi students of sd Negeri 173105 tarutung, north tapanuli the regency year 2019.  This study used quantitative inferential research methods. The research population was all grade VI students of SD Negeri 173105 Tarutung who were Christian, amounting to 56 people. The research sample is taken the entire population so that this study is a population study. The research instrument was a closed questionnaire. The questionnaire trial was conducted on 10 fifth grade students at SD Negeri 173131 Tarutung.The research data were analyzed using descriptive and inferential statistical data analysis techniques with the following steps: 1) The relationship test found that r count r table was 0.673 0.266. It can be concluded that there is a positive relationship between Giving Strengthening with Learning Motivation of PAK Grade VI Students of SD Negeri 173105 Tarutung in 2019, 2) Significant test of the relationship is known that t count t table is 6.691 2,000. It can be concluded that there is a positive and significant relationship of strengthening the gift of Christian education teacher with students learning motivation for class vi students of sd negeri 173105 tarutung, north tapanuli the regency year 2019. Kata Kunci: Strengthening Gift, Students Learning Motivation